Efficient evaluation of frequently issued similar XPath queries - Ong, Chin Sin. (2009)
Extensible Markup Language (XML) is a format for defining data exchange. It has gained high popularity in the recent years but has yet to be efficiently and effectively handled. This project aims to efficiently evaluate query expressions that are similar and frequently issued. The project is built on XCalibur, a system that uses a novel schema to manage XML documents in Relational Database Management Systems (RDBMS). We propose an algorithm to utilize the results of similar past queries to increase the querying capability of XCalibur. A performance analysis is done to demonstrate the results obtained by comparing the algorithm with XCalibur. We concluded that our work does improve the query translation and present the results of our findings. Finally, the limitations and the possibilities of extension of this project are discussed.